Educational Literacy Movement Through The Establishment Of A Reading Corner At SMKS Nusantara Banyuwangi - Nurul Yunda Nanik Purwanti; Setiawan, Donny; Farhanto, Galih; Setyaningsih, Puji; Mukhtarsyaf, Fahd (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Reading corners are a way to bring books closer to students. The 6th Army Teaching Campus in collaboration with the students of SMKS Nusantara Banyuwangi created the Pojok Read program as a means to increase the reading interest of pupils. Research methods that use qualitative descriptive methods which use data collection methods such as observations, interviews and documentation. The results of the research showed that the Making of a Reading Claw at NUSANTARA BANYUWANGI SMKS contributed positively to the increased interest of students in reading. By providing a pleasant and comfortable space for reading so that it affects student learning achievements. With the presence of Reading Corner, it is possible to implement the School Literacy Movement that can develop student reading skills and absorb information from reading to improve student academic achievement in a variety of subjects.